2004
DOI: 10.1130/g20079.1
|View full text |Cite
|
Sign up to set email alerts
|

Fossil whale preservation implies high diatom accumulation rate in the Miocene–Pliocene Pisco Formation of Peru

Abstract: Diatomaceous deposits in the Miocene-Pliocene Pisco Formation contain abundant whales preserved in pristine condition (bones articulated or at least closely associated), in some cases including preserved baleen. The well-preserved whales indicate rapid burial. The 346 whales within ϳ1.5 km 2 of surveyed surface were not buried as an event, but were distributed uninterrupted through an 80-m-thick sedimentary section. The diatomaceous sediment lacks repeating primary laminations, but instead is mostly massive, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 17 publications
5
45
0
Order By: Relevance
“…Brand, Esperante, Chadwick, Poma Porras, & Alomía, 2004;Ehret et al, 2012;Esperante, Brand, Chadwick, & Poma, 2015;Esperante, Brand, Nick, Poma, & Urbina, 2008;Gariboldi et al, 2015;Lambert, Bianucci, & de Muizon, 2008;Lambert, Bianucci, & Post, 2009Lambert, Bianucci, Post, de Muizon, et al, 2010;Lambert, Bianucci, & Beatty, 2014;Lambert, de Muizon, & Bianucci, 2014;Lambert et al, 2015;Collareta et al, 2015). However, despite the growing significance of the vertebrate fauna of the Pisco Formation, a comprehensive stratigraphic framework for individual fossil-bearing localities and their position relative to one another has yet to be established (Brand, Urbina, Chadwick, DeVries, & Esperante, 2011;Di Celma et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Brand, Esperante, Chadwick, Poma Porras, & Alomía, 2004;Ehret et al, 2012;Esperante, Brand, Chadwick, & Poma, 2015;Esperante, Brand, Nick, Poma, & Urbina, 2008;Gariboldi et al, 2015;Lambert, Bianucci, & de Muizon, 2008;Lambert, Bianucci, & Post, 2009Lambert, Bianucci, Post, de Muizon, et al, 2010;Lambert, Bianucci, & Beatty, 2014;Lambert, de Muizon, & Bianucci, 2014;Lambert et al, 2015;Collareta et al, 2015). However, despite the growing significance of the vertebrate fauna of the Pisco Formation, a comprehensive stratigraphic framework for individual fossil-bearing localities and their position relative to one another has yet to be established (Brand, Urbina, Chadwick, DeVries, & Esperante, 2011;Di Celma et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Soft tissue preservation, while rare, does occur. Several instances of baleen preservation have been noted (e.g., Brand et al, 2004), but no other soft tissues of fossil marine mammals have been reported. Thus, any interpretation of the behavior of fossil marine mammals must be reflected in the morphology of the skeleton or teeth, be reflected in modification of the skeleton or teeth, or be interpreted from the depositional context of the fossils.…”
Section: Methodsmentioning
confidence: 99%
“…The first attempt to census the fossil vertebrates in the Pisco Formation was made by Muizon and DeVries (1985). Two decades later, Brand, Esperante and colleagues (Brand, Esperante, Chadwick, Poma, and Alomía, 2004;Esperante, Brand, Nick, Poma, and Urbina, 2008;Esperante, Brand, Chadwick, & Poma, 2015), evidenced an extraordinary concentration of specimens in several localities of the Pisco Formation, but these papers were limited to baleen whales and, consequently, did not provide any useful information about the faunal diversity of these highly fossiliferous areas. With a different approach, Brand, Urbina, Chadwick, DeVries, and Esperante (2011) attempted to place some published fossil vertebrates of the Pisco Formation along several measured stratigraphic sections; their work provided a rough indication of the fossil distribution, only reporting a non-exhaustive list of fossils, some of which were not correctly placed along the stratigraphic sections (Lambert & Muizon, 2014).…”
Section: Introductionmentioning
confidence: 99%